2020
DOI: 10.1371/journal.pone.0242619
|View full text |Cite
|
Sign up to set email alerts
|

The sound of reading: Color-to-timbre substitution boosts reading performance via OVAL, a novel auditory orthography optimized for visual-to-auditory mapping

Abstract: Reading is a unique human cognitive skill and its acquisition was proven to extensively affect both brain organization and neuroanatomy. Differently from western sighted individuals, literacy rates via tactile reading systems, such as Braille, are declining, thus imposing an alarming threat to literacy among non-visual readers. This decline is due to many reasons including the length of training needed to master Braille, which must also include extensive tactile sensitivity exercises, the lack of proper Braill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 79 publications
(117 reference statements)
1
3
0
Order By: Relevance
“…Specifically, we suggest that the addition of the ‘color’ feature to soundscapes might have provided another discrimination feature among auditory pixels, and thus might have increased discriminability among face features. Crucially, these results are in line with another recent work from our team which similarly showed that color-to-timbre mapping enhanced discrimination of auditory letters and boosts reading performance via the EyeMusic SSD compared to identical monochrome soundscapes 16 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Specifically, we suggest that the addition of the ‘color’ feature to soundscapes might have provided another discrimination feature among auditory pixels, and thus might have increased discriminability among face features. Crucially, these results are in line with another recent work from our team which similarly showed that color-to-timbre mapping enhanced discrimination of auditory letters and boosts reading performance via the EyeMusic SSD compared to identical monochrome soundscapes 16 .…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, color is known to enhance discriminability of images, especially in lower resolutions, and has been directly shown to enhance real-life face identification in the context of low visual resolution 15 . While it is difficult to directly project on the blind population the same color-related benefits, we reasoned that the EyeMusic color-transformation may facilitate the differentiation among auditory face features, i.e., similarly to what color does for hard visual tasks (see also 16 showing the benefits of adding the EyeMusic color feature to the reading of words composed of letters from a newly learned SSD alphabet).…”
Section: Introductionmentioning
confidence: 99%
“…The word training aimed at teaching our participants a novel orthography that we created by merging Braille and Morse features and transformed via EyeMusic to soundscapes (for full details see Arbel et al, 2020 ). During this structured training program, participants learned to read using this new orthography.…”
Section: Methodsmentioning
confidence: 99%
“…To teach participants the perception of the much more complicated colorful face soundscapes, we designed a ∼12 h training program specifically tailored to teach the perception of face shapes in their upright orientation, alongside additional similarly long training targeting other “visual” categories. Specifically, we trained our participants to perceive short words via SSD using a novel auditory SSD alphabet we developed ( Arbel et al, 2020 ). This allowed us to explore the role of subordinate object identification associated with face exemplars, as well as experience with a novel category of stimuli ( Gauthier and Tarr, 1997 ; Gauthier et al, 1999 , 2000a ).…”
Section: Introductionmentioning
confidence: 99%